1999
DOI: 10.1590/s0100-736x1999000300002
|View full text |Cite
|
Sign up to set email alerts
|

Resistência anti-helmíntica em rebanhos caprinos no Estado do Ceará

Abstract: Pesq. Vet. Bras. 19(3/4):99-103, jul./dez. 1999 99 RESUMO.-Um levantamento em nível de campo sobre resistência anti-helmíntica em nematódeos gastrintestinais de caprinos foi realizado em 34 rebanhos no Estado do Ceará. Em cada rebanho foram separados 30 cabritos, de ambos os sexos, com idade variando de 1 a 6 meses, os quais foram individualmente pesados, identificados e distribuídos em três tratamentos: 1) Oxfendazole na dose de 4,75mg/kg; 2) Levamisole na dose de 7,5 mg/kg e 3) Controle (não medicado). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
17

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 21 publications
1
5
0
17
Order By: Relevance
“…In another experiment, Vieira et al (1992) demonstrated the loss of effectiveness of ivermectin and of a pre-benzimidazole (netobimin) in sheep brought from the south, raising the question of exchanges of parasitic populations among regions. In the late 90s, Vieira & Cavalcante (1999) corroborated the findings published in 1989, including results of resistance to levamisole and oxfendazole in 34 goat herds in CE. Melo et al (1998) detected resistance to ivermectin and closantel in goats and to oxfendazole and closantel in sheep.…”
Section: Northeast Regionsupporting
confidence: 83%
See 1 more Smart Citation
“…In another experiment, Vieira et al (1992) demonstrated the loss of effectiveness of ivermectin and of a pre-benzimidazole (netobimin) in sheep brought from the south, raising the question of exchanges of parasitic populations among regions. In the late 90s, Vieira & Cavalcante (1999) corroborated the findings published in 1989, including results of resistance to levamisole and oxfendazole in 34 goat herds in CE. Melo et al (1998) detected resistance to ivermectin and closantel in goats and to oxfendazole and closantel in sheep.…”
Section: Northeast Regionsupporting
confidence: 83%
“…Albendazole presented higher effectiveness in goats (VIEIRA et al, 1989) only when compared to the other benzimidazoles or when compared to ivermectin, in a test carried out on sheep and goats by Pereira et al (2008); even so, its effectiveness rate in this review did not exceed 70%. Oxfendazole likewise showed effectiveness only in goats when compared to the other benzimidazoles (VIEIRA et al, 1989), or was found to be more effective than levamisole on one farm, in a study by Vieira & Cavalcante (1999). In sheep, oxfendazole was studied separately by Melo et al (2004Melo et al ( , 2009, showing low effectiveness rates over the years in CE.…”
Section: Developments In Research and The Effectiveness Of Anthelmintmentioning
confidence: 99%
“…Média da redução do número de ovos por grama de Quadro 1. Média da redução do número de ovos por grama de fezes (OPG) de nematóides gastrintestinais e percentual médio fezes (OPG) de nematóides gastrintestinais e percentual médio fezes (OPG) de nematóides gastrintestinais e percentual médio fezes (OPG) de nematóides gastrintestinais e percentual médio fezes (OPG) de nematóides gastrintestinais e percentual médio da eficácia de drogas anti-helmínticas em caprinos fêmeas na da eficácia de drogas anti-helmínticas em caprinos fêmeas na da eficácia de drogas anti-helmínticas em caprinos fêmeas na da eficácia de drogas anti-helmínticas em caprinos fêmeas na da eficácia de drogas anti-helmínticas em caprinos fêmeas na mesorregião do Sertão P mesorregião do Sertão P mesorregião do Sertão P mesorregião do Sertão P mesorregião do Sertão Paraibano em diferentes períodos de araibano em diferentes períodos de araibano em diferentes períodos de araibano em diferentes períodos de araibano em diferentes períodos de obser obser obser obser observação vação vação vação vação (Melo et al 1998, Vieira & Cavalcante 1999, no nordeste brasileiro (Barreto & Silva 1999). Provavelmente, esses nematóides desenvolvem resistência mais rápida, devido ao seu alto potencial biótico (Echevarria & Trindade 1989).…”
Section: Resul Resul Resul Resul Results T T T Tados E Discus Ados E Dunclassified
“…A difusão ineficiente no repasse de tecnologias e utilização terapêutica iatrogênica das drogas antiparasitárias em ruminantes tem contribuído para a resistência anti-helmíntica (RA) em várias regiões produtoras do país (Echevarria et al 1996, Vieira & Cavalcante 1999.…”
unclassified
See 1 more Smart Citation